Cost Analysis of a School-Based Social and Emotional Learning and Literacy Intervention1. Issue 3 (10th April 2015) - Long, Katherine; Brown, Joshua L.; Jones, Stephanie M.; Aber, J. Lawrence; Yates, Brian T.
Abstract : Purpose : There is limited research on the costs of social and emotional learning (SEL) interventions [Crowley, Jones, Greenberg, Feinberg & Spoth (2012). Resource Consumption of a Diffusion Model for Prevention Programs: The PROSPER Delivery System. Journal of Adolescent Health, 50 (3), 256–263]. This paper describes a comprehensive methodology for determining the costs of a successful universal, school-based SEL intervention that was implemented in nine public schools over 3 years. Methods : Resource costs were identified using the Cost–Procedure–Process–Outcome Analysis Model [Yates (1996). Analyzing Costs, Procedures, Processes, and Outcomes in Human Services. Thousand Oaks, CA, US: Sage Publications, Inc.; Yates (1999). Measuring and Improving Cost, Cost-Effectiveness, and Cost-Benefit for Substance Abuse Treatment Programs . No. NIH 99-4518, 135] and the ingredients model [Levin (Ed.) (1983). Cost-Effectiveness A Primer (Vol. 4). Beverly Hills, CA: Sage; Levin & McEwan (2001). Cost-Effectiveness Analysis: Methods and Applications . (2nd ed.). Thousand Oaks, CA: Sage Publications]. This involved careful identification of resource use, finding the cost per unit for each resource by intervention activity, and ultimately calculating the total resource cost (resource use $×$ cost per unit). Results : Our analysis estimated the overall cost of this 3-year SEL and literacy intervention to be $1, 831, 296 for nine schools. This averages to $67, 825 yearly per school and $130 yearly for each student. The analysis estimated the first year of the intervention to be the costliest ($683, 106) and then decreasing in Year 2 ($581, 764) and Year 3 ($566, 426). Conclusion : This research emphasizes the need to study the costs of SEL interventions. By providing a detailed and standardized methodology, this cost analysis can provide added support for implementing an effective social and emotional learning intervention in a school setting. Furthermore, it provides groundwork for more advanced cost analyses, such as a cost–effectiveness analysis or a benefit-cost analysis (BCA).